Histological regression of peritoneal metastases of recurrent tubo-ovarian cancer after systemic chemotherapy - Pache, Basile; Teixeira Farinha, Hugo; Toussaint, Laura; Demartines, Nicolas; Hastir, Delfyne; Mathevet, Patrice; Sempoux, Christine; Hübner, Martin (Frontiers in Surgery, 2022)
Introduction Post-treatment histological regression of peritoneal metastases (PM) is a new and potentially important predictor of oncological outcomes. Histology of PM from adnexal origin is usually evaluated by the Chemotherapy Response Score (CRS). The aim of this preliminary study was to quantify the response of PM of recurrent tubo-ovarian cancer (TOVC) after systemic chemotherapy by using the recently validated Peritoneal Regression Grading System (PRGS) and compare it with CRS. Correlation with per operative evaluation through Peritoneal Cancer Index (PCI) was performed. Material and methods Retrospective cohort study of all consecutive patients with recurrent PM from TOVC undergoing surgery after prior systemic chemotherapy from January 2015 to March 2019. Biopsies were assessed with the four-scale PRGS. Results Thirty-eight patients were included. Patients had a median of 2 (range 1–2) lines and 12 (range 3–18) cycles of prior systemic chemotherapy. Overall mean (SD) PRGS was 2.3 (±1.1). Of the patients, 26% (10) had complete response (PRGS 1), 40% (15) had major response (PRGS 2), 26% (10) minor response (PRGS 3), and 8% (3) had no response (PRGS 4). Mean PRGS was positively correlated with the Peritoneal Cancer Index (ρ = 0.5302, p = 0.0003) and inversely correlated with CRS (ρ = −0.8403, p < 0.0001). No correlation was highlighted between mean PRGS and overall survival (ρ = −0.0195, p = 0.9073). Conclusion CRS and mean PRGS correlated with each other. Histological response of PM after systemic chemotherapy was quantifiable and variable. The role of PRGS for the evaluation of treatment response and as potential surrogate marker for oncological outcomes is part of ongoing and planned research.